1999
DOI: 10.5005/jcdp-1-4-34
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dentist-Prescribed, Home-Applied Tooth Whitening, A Meta-analysis

Abstract: Introduction Common clinical experience suggests that tooth whitening agents are 100% effective. This study uses meta-analysis of data from published randomized controlled clinical trials to determine the efficacy of tooth whitening agents. Methods A MEDLINE search strategy was developed and implemented to systematically identify clinical trials on dentist-prescribed, home-applied tooth whitening agents, using 10% carbamide peroxide, published between 1989-1999. Inclusion criteria (e.g., in English, human cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In addition, 20% of subjects who used the peroxide product achieved a mean change of five shade guide units. 105 Ishikawa-Nagai et al 106 evaluated the tooth colour change of 80 subjects after using 10% carbamide peroxide in a gum shield over 14 days and found a strong correlation between total colour change and b * values, demonstrating that bleaching works efficiently for teeth with a yellow hue. Further, an analysis of the clinical results with over 600 subjects undergoing tooth bleaching, indicate that the yellower the teeth at baseline, the greater the magnitude of the whitening response.…”
Section: Other Factorsmentioning
confidence: 97%
“…In addition, 20% of subjects who used the peroxide product achieved a mean change of five shade guide units. 105 Ishikawa-Nagai et al 106 evaluated the tooth colour change of 80 subjects after using 10% carbamide peroxide in a gum shield over 14 days and found a strong correlation between total colour change and b * values, demonstrating that bleaching works efficiently for teeth with a yellow hue. Further, an analysis of the clinical results with over 600 subjects undergoing tooth bleaching, indicate that the yellower the teeth at baseline, the greater the magnitude of the whitening response.…”
Section: Other Factorsmentioning
confidence: 97%
“…The full texts of these 29 studies were assessed to check if they were eligible. Among them, 16 were excluded due to the following reasons: (1) old systematic reviews [ [13,21]], (2) case series studies [ [22]], (3) placebocontrolled studies [ [23][24][25]], (4) studies that did not compare PC and PH products [ [26][27][28][29][30][31]], and (5) studies that did not employ a control tray-delivered CP product [32][33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
“…At‐home vital bleaching is probably the safest, most patient‐pleasing method of obtaining effective tooth bleaching because of the noninvasive nature of this treatment. The most commonly employed active ingredient is 10% CP gel, which has shown satisfactory clinical results 7–9 . A meta‐analysis of seven clinical studies indicated a significant mean change from baseline of 6.4 shade guide units according to the Vitapan Vita guide scale by the use of tray‐based bleaching systems utilizing 10% CP gels 7 …”
Section: Introductionmentioning
confidence: 99%
“…The most commonly employed active ingredient is 10% CP gel, which has shown satisfactory clinical results. [7][8][9] A meta-analysis of seven clinical studies indicated a significant mean change from baseline of 6.4 shade guide units according to the Vitapan Vita guide scale by the use of tray-based bleaching systems utilizing 10% CP gels. 7 Although the overnight bleaching with the application of 10% CP exhibited desirable whitening effects, the long duration of the treatment directed the manufacturers toward developing new systems with shorter treatment times and with CP concentrations higher than 10%.…”
Section: Introductionmentioning
confidence: 99%